ASYMPTOTIC ESTIMATES ON A SMALL PARAMETER IN HARTMANN-WINTNER LAW OF ITERATED LOGARITHM - M. U. Gafurov (American Journals, 2023)
An asymptotic estimate of the convergence velocity in the law of repeated logarithm in the form of convergence of series from the probabilities of large evasions is obtained.
Keywords: the law of repeated logarithm, the convergence of the series, the number of outputs, the normal law, the speed of convergence in the central limit theorem